Pelajaran dari Apartheid: Membangun Kewarganegaraan yang Adil melalui Pemahaman Antropologis - Berlian, Nur; Febriani, Rika (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This paper explores the link between anthropological views on race and citizenship politics, focusing on South Africa's Apartheid. Before the 1800s, non-European societies were often unfairly labeled